2009
DOI: 10.3748/wjg.15.5966
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma of the middle bile duct: Is bile duct segmentalresection appropriate?

Abstract: AIM:To compare survival between bile duct segmental resection (BDSR) and pancreaticoduodenectomy (PD) for treating distal bile duct cancers. METHODS:Retrospective analysis was conducted for 45 patients in a BDSR group and for 149 patients in a PD group. RESULTS:The T-stage (P < 0.001), lymph node invasion (P = 0.010) and tumor differentiation (P = 0.005) were significant prognostic factors in the BDSR group. The 3-and 5-year overall survival rates for the BDSR group and PD group were 51.7% and 36.6%, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 28 publications
(42 reference statements)
1
26
0
Order By: Relevance
“…Moreover, MMP1 appears to be a key determinant that selectively mediates lung metastasis in a murine breast cancer model (Minn et al, 2005, 2007; Nguyen and Massague, 2007). MMP13 (collagenase-3) originally identified in human breast cancer tissue (Freije et al, 1994) is viewed as a potential tumor marker for breast cancer diagnosis (Chang et al, 2009) and its expression is correlated with metastasis formation (Ellsworth et al, 2009; Lee et al, 2009). In experimental models, MMP13 appears as a key stromal mediator of cancer progression that regulates the release of angiogenic factors (Lederle et al, 2009) and metastatic dissemination (Zigrino et al, 2009).…”
Section: Collagen Remodelingmentioning
confidence: 99%
“…Moreover, MMP1 appears to be a key determinant that selectively mediates lung metastasis in a murine breast cancer model (Minn et al, 2005, 2007; Nguyen and Massague, 2007). MMP13 (collagenase-3) originally identified in human breast cancer tissue (Freije et al, 1994) is viewed as a potential tumor marker for breast cancer diagnosis (Chang et al, 2009) and its expression is correlated with metastasis formation (Ellsworth et al, 2009; Lee et al, 2009). In experimental models, MMP13 appears as a key stromal mediator of cancer progression that regulates the release of angiogenic factors (Lederle et al, 2009) and metastatic dissemination (Zigrino et al, 2009).…”
Section: Collagen Remodelingmentioning
confidence: 99%
“…This was a hilar cholangiocarcinoma not invading other structures or adjacent organs. Therefore, limited surgical resection was justified as has been reported by Hyung et al [6]. The functional and oncological outcomes of complete laparoscopic surgery were found to be adequate.…”
Section: Discussionmentioning
confidence: 78%
“…First, we classified extrahepatic BD cancer as DISTAL (confined to intrapancreatic BD) and MID/DIFFUSE (involving extrapancreatic BD). Previous studies have classified middle BD cancer as tumors confined to the mid BD (MID group in our study) which could be treated with BD resection, and distal BD cancer as involvement with the intrapancreatic portion of the BD or diffuse BD cancer (DISTAL and DIFFUSE group in this study), in which PD was necessary [ 9 , 15 ]. In others, tumors were classified by the predominant location of the tumor without considering diffuse bile duct cancer, DIFFUSE in our study [ 5 , 13 ].…”
Section: Discussionmentioning
confidence: 98%
“…In the tumor is confined to the middle BD, there have been debates about whether segmental BD resection is an adequate operative procedure or not [ 6 ]. A few studies have shown that similar incidence of positive surgical margin and similar long-term results between segmental BD resection and PD in the cancer confined to middle BD [ 7 , 15 , 26 , 28 ]. Our results showed that the clinical characteristics and long-term results between MID and DIFFUSE were not different, and the long-term results according to the operative procedure, either BD resection or PD in these groups, were also similar (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation